Economic and environmental evaluation of a small-scale biogas plant: Case study in the Chillon Valley, Peru. - Pinares Buendia, José Santos; Samaniego Nolasco, Jose Alberto; Patiño Vidal, Carlos Diego; Carhuancho Leon, Fanny Mabel; Rodríguez Rodríguez, Berlan; Jiménez Borges, Reinier; Castillo Alvarez, Yoisdel (LACCEI, 2025)
The economic and environmental evaluation of decentralized energy technologies is crucial for sustainable development in rural communities. In this context, an evaluation of financial indicators and a Life Cycle Assessment (LCA) is carried out for a small-scale biogas plant in the Chillon Valley, Peru. The research uses an experimental and analytical approach, evaluating a 770 liter biodigester, with a useful volume of 640 liters and a hydraulic retention time of 20 days. The daily feed consists of 4 kg of organic matter (70 kg of cow excreta and 30 kg of organic waste), together with 12 liters of water. The average biogas production is around 255 liters/day, generating 14 liters/day of biofertilizer. From an economic perspective, the initial investment in the system was US2,030, resulting in a Payback Period (payback period) of 2.67 years, evidencing its rapid profitability. The Life Cycle Assessment (LCA), according to ISO 14040 and 14044 standards, compared the environmental impact of biogas, Liquefied Petroleum Gas (LPG) and firewood in cooking food. The results showed that biogas reduces by 1.5 tons of CO_2 equivalent per ton of waste treated and reduces by 23% the formation of particulate matter (PM2.5), thus improving air quality and human health. The biogas plant in the Chillon Valley represents a sustainable alternative that could be expanded in rural areas, promoting energy independence both in Peru and globally, offering an efficient, economically and environmentally viable solution that contributes to an energy transition through a circular economy model.